2021
DOI: 10.1186/s12929-021-00748-0
|View full text |Cite
|
Sign up to set email alerts
|

Chandipura virus dysregulates the expression of hsa-miR-21-5p to activate NF-κB in human microglial cells

Abstract: Background Chandipura virus (CHPV) is a negative single-stranded RNA virus of the Rhabdoviridae family. CHPV infection has been reported in Central and Western India. CHPV causes acute encephalitis with a case fatality rate of 70 % and mostly affects children below 15 years of age. CHPV infection in brain leads to neuronal apoptosis and activation of the microglial cells. The microRNAs (miRNAs) are small endogenous non-coding RNA that regulate the gene expression. Viral infections perturb the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
(84 reference statements)
1
6
0
2
Order By: Relevance
“…The study showed that the microRNA upregulation suppress PTEN expression and activate NF-ĸB through PI3K/AKT pathway. NF-ĸB activation induce pro-inflammatory responses and may participate in CHPV induced neuroinflammation (Pandey et al 2021).…”
Section: Mir-21-5pmentioning
confidence: 99%
“…The study showed that the microRNA upregulation suppress PTEN expression and activate NF-ĸB through PI3K/AKT pathway. NF-ĸB activation induce pro-inflammatory responses and may participate in CHPV induced neuroinflammation (Pandey et al 2021).…”
Section: Mir-21-5pmentioning
confidence: 99%
“…1 It is a vector-borne virus in the family Rhabdoviridae that is transmitted by the sand fly species Phlebotomus sp., Sergentomyia sp., and the mosquito Aedes aegypti. 2 CHPV primarily replicates in neurons, which can lead to neuroinflammation and neuronal cell death. 2 In pediatric patients, the fatality rate of CHPV infection ranges from 44% to 75%.…”
Section: In Vitro and In Vivo Testing Of The Antiviral Effect Of Favi...mentioning
confidence: 99%
“…2 CHPV primarily replicates in neurons, which can lead to neuroinflammation and neuronal cell death. 2 In pediatric patients, the fatality rate of CHPV infection ranges from 44% to 75%. 3 Severe CHPV infection is characterized by high-grade fever, vomiting, and convulsions that can lead to coma and death within 48 h of hospitalization.…”
Section: In Vitro and In Vivo Testing Of The Antiviral Effect Of Favi...mentioning
confidence: 99%
“…Los miRNA pueden clasificarse como provirales (cuando favorecen la replicación viral y la infección) o antivirales, según las acciones que ejerzan en sus genes blanco una vez que el virus ha entrado en la célula huésped (53). Se ha identificado la sobreexpresión de miR-21 en infecciones por virus de la hepatitis B y C, papiloma, Epstein Barr, chandipura y dengue (54,55). En la infección por virus chandipura, que ocasiona una encefalitis aguda, la sobreexpresión de hsa-miR-21-5p condujo a la disminución de la expresión de PTEN posterior activación de la vía de señalización PI3K/AKT que promueve a su vez la activación de NF-ĸB y la respuesta proinflamatoria (55).…”
Section: Infeccionesunclassified